Paecilomyces lilacinus causing debilitating sinusitis in an immunocompetent patient: a case report - Wong, Gentle (BioMed Central, 2012)
INTRODUCTION: Since the discovery of the first documented case of Paecilomyces in 1963, only five cases of Paecilomyces sinusitis have been described to date and all of them have predisposing factors such as immunocompromised status or prior nasal surgery. We present the first case of Paecilomyces lilacinus sinusitis in a fit young woman with no identified predisposing factors. To the best of our knowledge, this is the first known case in the UK and in Europe. CASE PRESENTATION: A 20-year-old Iraqi woman who has lived in the UK for the past five years presented with rhinorrhea, hyposmia, and nasal obstruction. She was previously fit and well and had no significant medical history. Imaging revealed a fungal infection that was eventually revealed on cytological examination to be P. lilacinus. CONCLUSIONS: P. lilacinus is both a difficult and important organism to identify because it has intrinsic anti-fungal resistance. In our case, the infection was severe and recurrent, and the organism demonstrated resistance to common oral anti-fungal agents. There was a delay in its diagnosis, owing to its similarity in appearance to Penicillium and a difficulty in distinguishing between the two without specialized knowledge of fungal taxonomy. In the field of otolaryngology, Paecilomyces is relatively unknown. Our intention is to raise awareness of this organism as well as to describe the challenges in its management.